Omalizumab as monotherapy for food allergy. Issue 3 (June 2021) - Arasi, Stefania; Mennini, Maurizio; Cafarotti, Arianna; Fiocchi, Alessandro
Abstract : Purpose of review: To familiarize the reader with the most recent insights in the use of Omalizumab (monoclonal anti-immunoglobulin E) monotherapy in the treatment of patients with severe food allergy. Recent findings: The current data from early stage clinical trials show that Omalizumab may be safe and effective by itself in providing desensitization to one or several foods without requiring allergen exposure. Summary: In the near future, advances in knowledge will guide the adoption and implementation of any new therapy for food allergy and allow the development of a personalized treatment tailored on the specific patient's profile.